Model Berbasis Aturan untuk Transliterasi Bahasa Jawa dengan Aksara Latin ke Aksara Jawa - Aditya Wikan Mahastama (Jurnal Buana Informatika, 2022)
Abstract. Rule-Based Model for Javanese Language Text Transliteration from Latin to Javanese Script. Computer technologies today have reached an applicable level to aid with language learning and translation. These technologies should also be helpful in learning traditional languages that are getting forgotten due to globalisation. With its rich cultural diversity, Indonesia facesthe same fate asits regional languages. Javanese, for example, is declining in its proper usage in written and spoken language. This research aims to provide a rule-based model for transliterating Javanese words written in Latin to Javanese script using Unicode. The model is based on extracted rules in writing the script to make it possible to be used as a model for other similar Nusantara scripts. The model yields 96,44% accuracy rate, which is adequate to provide decent transliteration for basic Javanese language learners and is open for additional rules to improve its ability to transliteratemore complex structures, contexts, as well rules for different Nusantara languages. Keywords: Rule-based model, Syllabification, Transliteration, Javanese Abstrak. Teknologi komputer masa kini telah mencapai kemajuan yang dapat membantu pembelajaran dan penerjemahan bahasa. Teknologi ini selayaknya juga dapat dimanfaatkan untuk membantu pelestarian bahasa-bahasa daerah yang semakin terlupakan. Indonesia dengan berbagai suku bangsanya juga menghadapi masalah dengan menurunnya penggunaan bahasa daerah, misalnya Bahasa Jawa. Penelitian ini mengusulkan sebuah model berbasis aturan untuk alih aksara teks berbahasa Jawa dari aksara Latin ke aksara Jawa Unicode. Model ini didasarkan pada ekstraksi aturan penulisan aksara Jawa, dengan harapan agar dapat digunakan sebagai model transliterasi bahasa-bahasa Nusantara yang serupa. Hasil uji dengan tingkat akurasi sebesar 96,44% menunjukkan bahwa model ini mampu melakukan transliterasi untuk pembelajar aksara Jawa dasar, mudah diduplikasi dan dapat dikembangkan untuk menyempurnakan kemampuannya untuk mengenali sruktur dan konteks yang lebih kompleks.Kata Kunci: Model berbasis aturan, Silabifikasi, Transliterasi, Bahasa Jawa.